The Influence of Product Quality, Price, and Promotion On The Interest In Buying Beauty Products On Brand Ms Glow - Suci Hestya Damayanti; Sintia Nurfadilah; Ramlah Puji Astuti (Journal Research of Social Science, Economics, and Management, 2024)
The cosmetic industry is growing rapidly today, where the cosmetic industry is one of the industries in Indonesia that has succeeded in dominating the domestic market, one of which is MS Glow cosmetic products. This study aims to analyze the effect of product quality, price and promotion on buying interest. This research uses quantitative data analysis methods using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of SmartPLS 3.0 software. Primary data was collected by distributing questionnaires to 100 buyers and users of MS Glow products, especially those in Cirebon City. All hypotheses proposed are supported and significant. (1) Product quality has a positive and significant effect on buying interest, (2) Price has a positive and significant effect on buying interest, (3) promotion has a positive and significant effect on buying interest.